Guesthouse customer satisfaction analysis using quantitative kano model - Ng, Pei Wen (Universiti Malaysia Sarawak (UNIMAS), 2015)
Customer satisfaction is the biggest contemporary challenge in the service industries. Service quality and customer satisfaction are generally regarded as the key factors in influencing the loyalty and customer retention. A good perception is retained when an organization supplies goods and services to customers in a manner that satisfies them. The purpose of this study is to determine customer satisfaction in the guesthouse industry. This study adopts quantitative Kano model to classify and prioritize customer needs based on survey data using a set of questionnaires that consists of eight service quality factors and eleven facility quality factors of the guesthouse industry. The results of this study show that guesthouse should pay attention on free tours information and tour operator services and fast treatment of customer complaint issues as it will result as customer dissatisfaction when they are absent. Furthermore, the services of providing fruit basket in room upon arrival and different designs for each room able to delight customers. The overall study has meaningful implications on management decision making in the guesthouse industry.